CTNI-13. MALIGNANT GLIOMA SUBSET FROM ACTUATE 1801 PHASE 1/2 STUDY OF 9-ING-41, A GLYCOGEN SYNTHASE KINASE 3 BETA (GSK-3β) INHIBITOR, AS A SINGLE AGENT AND COMBINED WITH CHEMOTHERAPY REFRACTORY. (12th November 2021) - Odia, Yazmin; Cavalcante, Ludimila; Safran, Howard; Powell, Steven Francis; Munster, Pamela; Ma, Wen Wee; Carneiro, Benedito; Bastos, Bruno; Giles, Francis; Sahebjam, Solmaz
Abstract: BACKGROUND: GSK3β serine/threonine kinase regulates metabolism and glycogen biosynthesis. GSK3β overexpression promotes tumor progression and resistance through NF-κB and p53 apoptotic pathways. GSK3β inhibits immunomodulation by downregulating checkpoints, e.g. PD-L1 and LAG-3, and increasing NK and T-cell mediated tumor killing. 9-ING-41 is a small-molecule, potent, selective GSK3β inhibitor with preclinical activity. In chemoresistant PDX glioblastoma models, 9-ING-41 enhanced lomustine antitumor effect. METHODS: Patients with refractory malignancies were treated with 9-ING-41 monotherapy (n=65) or combined with 8 cytotoxic regimens after prior exposure (n=162) in the first-in-human study (NCT03678883). The recurrent gliomas subset was treated with 9-ING-41 monotherapy IV TIW q21day cycles at 3.3, 5, 9.3, 15mg/kg, or combined with lomustine 30 mg/m² PO weekly q84day cycles. Primary objective was safety and tolerability. RESULTS: An RP2D of 15mg/kg IV TIW was confirmed across all 9 regimens, no accentuation of chemotherapy toxicity noted. Of 18 glioma patients enrolled, 13 were glioblastoma, 2 anaplastic astrocytomas, 1 anaplastic oligodendroglioma, and 1 diffuse astrocytoma; 6 female, 12 male; median age 52 (30-69) years; median ECOG was 1 (0-2). All received initial radiation and temozolomide (18/18), prior salvage therapies included nitrosoureas (15/18), bevacizumab (8/18), TTFields (6/18), checkpoint inhibitor (4/18). Median recurrences 3 (1-6). NGS alterations included: IDH/wildtype (11), IDH/mutation(3); 1p19q/codeletion(10); MGMT/unmethylated(11), MGMT/methylated(1); EGFR/amplification(6), EGFR/v3mutation(3), TERT/mutation(6), PTEN/loss(3), NF1/rearrangement(2), ATRX/loss (2), TP53/mutation(4), CDKN2A/deletion(2), RB1/loss(1), PALB2/mutation(10). Four patients received 9-ING-41 monotherapy, 14 concurrently treated with lomustine. No SAEs or grade 3/4 AEs attributed to 9-ING-41 noted, only G1/2 vision changes (9/18, 50%), infusion reactions (4/18, 22%). Lomustine-related toxicities included G3/4 thrombocytopenia (3/14, 21%), and G1/2 fatigue (4/14, 28%). Median therapy duration was 55 (4-305); 1 partial response ( >50%) noted with 9-ING-41/lomustine. Median PFS and OS were 1.9 (0.3-11.1) and 6.0 (1.6-16.6) months, respectively. CONCLUSIONS: 9-ING-41 plus/minus lomustine is safe and warrants further study in glioma patients.